Characterization of the complete chloroplast genome of a Peruvian landrace of Capsicum chinense Jacq. (Solanaceae), arnaucho chili pepper - Arbizu Berrocal, Carlos Irvin (2022)
In this study, we sequenced the first complete chloroplast (cp) genome of a Peruvian chili pepper landrace, “arnacucho” (Capsicum chinense). This cp genome has a 156,931 bp in length with typical quadripartite structure, containing a large single copy (LSC) region (87,325 bp) and a 17,912 bp small single-copy (SSC) region, separated by two inverted repeat (IR) regions (25,847 bp); and the percentage of GC content was 37.71%. Arnaucho chili pepper chloroplast genome possesses 133 genes that consists of 86 protein-coding genes, 37 tRNA, eight rRNA, and two pseudogenes. Phylogenetic analysis revealed that this Peruvian chili pepper landrace is closely related to the undomesticated species C. galapagoense; all belong to the Capsiceae tribe.